Transformasi Kelembagaan dan Tata Kelola Perguruan Tinggi Keagamaan Islam Swasta: Studi Deskriptif Alih Bentuk Institut Menjadi Universitas Nahdlatul Ulama Bangil (UNUBA) - Dina Zuhrufia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The Ministry of Religious Affairs of the Republic of Indonesia is promoting large-scale transformation among more than 870 Private Islamic Religious Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Swasta/PTKIS) across Indonesia, including institutional transformation from institutes into universities. This article aims to describe and analyze the dynamics of institutional transformation and the governance structure of Nahdlatul Ulama University of Bangil (Universitas Nahdlatul Ulama Bangil/UNUBA), Pasuruan Regency, which officially transformed from the Nahdlatul Ulama Islamic Institute (Institut Agama Islam Nahdlatul Ulama/IAINU) Bangil into a university in February 2026. This study employs a descriptive qualitative approach based on document analysis and secondary data, including official institutional information from the university and official reports published by the Directorate General of Islamic Education of the Ministry of Religious Affairs during the 20252026 period, using the principles of Good University Governance as the analytical framework. The findings indicate that UNUBA's post-transformation governance structure has incorporated a clear division of managerial functions through three Vice Rectors responsible for academic affairs and human resources, finance and infrastructure, and student affairs and partnerships, respectively. The study also identifies indications of strengthened external accountability through the active involvement of the Regional Coordination Body for Islamic Higher Education (Kopertais) Region IV of East Java in supporting lecturer certification, visits by the Ministry of Religious Affairs to encourage the development of new study programs, and partnerships with the banking sector through corporate social responsibility programs as one strategy for diversifying resources. UNUBA's institutional transformation represents a broader pattern currently promoted by the Ministry of Religious Affairs at the national level, while also facing common challenges encountered by PTKIS following institutional transformation, particularly the advancement of lecturers' academic ranks and the standardization of governance practices.